2021
DOI: 10.1039/d0na00976h
|View full text |Cite
|
Sign up to set email alerts
|

Non-volatile conductive gels made from deep eutectic solvents and oxidised cellulose nanofibrils

Abstract: Ionogels offer huge potential for a number of applications including wearable electronics and soft sensors. However, their synthesis has been limited and often relies on non-renewable or non-biocompatible components. Here...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…24,25 This means that DESs can be extensively fine-tuned for specific applications and are cost-effective, green, and mostimportantly for biological applications, non-toxic. [26][27][28][29][30][31] In addition, many DESs are known glass formers which makes them extremely interesting for cryopreservation, and the potential role of natural deep eutectic solvents for desiccation and freezing tolerance in plants and animals has been mentioned in the literature. [32][33][34][35][36] Despite these promising properties, to date there have been few studies, to the authors' knowledge, exploring the use of DESs for cryopreservation of mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 This means that DESs can be extensively fine-tuned for specific applications and are cost-effective, green, and mostimportantly for biological applications, non-toxic. [26][27][28][29][30][31] In addition, many DESs are known glass formers which makes them extremely interesting for cryopreservation, and the potential role of natural deep eutectic solvents for desiccation and freezing tolerance in plants and animals has been mentioned in the literature. [32][33][34][35][36] Despite these promising properties, to date there have been few studies, to the authors' knowledge, exploring the use of DESs for cryopreservation of mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…23 interactions with certain types of analytes compared to [Ch + ][Cl − ], despite similarities in their chemical structures. 21,23 Previously, Bryant et al highlighted that the presence of a carboxylate substituent and the absence of hydroxyl functional groups, as well as their surfactant-like nature in betaine HBAs compared to [Ch + ][Cl − ], is responsible for varied electrostatic interactions, 26 thereby imparting differences in their solvation properties. Like all other classes of DESs, the polarity of zwitterionic DESs is strongly influenced by the type of HBA and HBD and/or their molar ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, due to the advantages of low cost, excellent biocompatibility, and high ionic conductivity over a wide temperature range (from subzero to high), ionic deep eutectic solvents have made great contributions to the progress of ionic gel sensors. Polymerizable deep eutectic solvents (PDESs) refer to the DES type formed by polymerizable hydrogen bond donors and hydrogen bond receptors. Elastomer materials that are transparent and stretchable can be obtained by polymerizing PDESs. Luna-Bárcenas et al first reported thermal-initiated polymerization of acrylic-acid/choline-chloride DESs, which provided a new idea for PDES-based conductive elastomers.…”
Section: Introductionmentioning
confidence: 99%